MEMFASILITASI MINAT BACA MASYARAKAT MELALUI PERPUSTAKAAN FISIK DAN DIGITAL DUSUN KARANGMOJO - Yudhy Widya Kusumo; Ratna Widyaningsih; Ristiyan Ragil Putradianto; Dewi Nur K.; Intan Zuhaira (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The current Covid-19 pandemic has caused children to study online. Thus, children are increasingly opening and playing gadgets. Not a few children spend their time just playing 'online games'. Adults who do activities or work from home on average spend their time using gadgets. With this phenomenon, people's interest in reading has decreased. One way to increase people's interest in reading is by making the Karangmojo Village Community Reading Corner. In the era of globalization as it is now, this Community Reading Corner not only provides a physical library but also provides a digital library that can be accessed via the Handy Library aplication by the people of Karangmojo Village.